Mothers' group participation: associations with social capital, social support and mental well‐being. (29th September 2015) - Strange, Cecily; Bremner, Alexandra; Fisher, Colleen; Howat, Peter; Wood, Lisa
Abstract: Aim: To investigate the relationships between participation in mothers' groups and social capital, social support and mental well‐being measures for mothers whose oldest child was 0‐5 years. Background: Evaluations of facilitated mothers' groups have found positive benefits for information sharing and support. Mothers' groups often continue as parent‐led groups; however, little is known about the potential benefits of ongoing participation compared with non‐participation. Design: Cross‐sectional survey. Methods: Data were collected through a survey from March 2013–January 2014 in Perth, Western Australia. The data from a subgroup of mothers ( N  =   313) whose oldest child was 0‐5 years of age were analysed using multivariable regression. Participation in mothers' groups in the previous 12 months was investigated for associations with social capital {Neighbourhood Cohesion Index (NCI); Families, Social Capital and Citizenship Survey (FSCCS) and Reciprocity}; social support {Medical Outcomes Study‐Social Support Survey (MOS‐SSS) and Parent Support Outside Home Scale (PSOHS)}; and mental well‐being {Warwick Edinburgh Mental Well‐Being Scale (WEMWBS)}. Participation was measured as three groups – locally, outside area of residence and non‐participation. Results: Mothers who participated in mothers' groups locally scored significantly higher than those who had not participated in mothers' group for 'social capital' (NCI, FSCCS, Reciprocity), 'social support' (MOS‐SSS, PSOHS) and 'mental well‐being' (WEMWBS). Mothers who participated in mothers' group outside the area scored significantly higher than those who had not participated in mothers' groups for one measure of 'social support' (PSOHS). Conclusions: Participation in mothers' group locally may provide support and social capital benefits for mothers of children aged 0‐5 years, which may influence mental well‐being.